Introduction to the Study of Mechanical Properties of Terpolymer PP/EPDM Mixtures - Scagliusi, Sandra R.; Carvalho, Elizabeth C.L.; Lugão, Ademar B. (Journal of Research Updates in Polymer Science, 2021)
Thermoplastic elastomers (TPEs), based in PP (Polypropylene) / EPDM (Ethylene Propylene Diene Monomer) have as purpose improving PP resistance and impact, aiming to a more comprehensive use in automotive market, among edifications, construction and packaging sectors, due to their recyclability properties. PP is a commodity, with a high melting point, high mechanical resistance and low density, posing a balance between physical and mechanical properties; in addition, it shows an easy processing, at low cost. In order to minimize this deficiency, EPDM, an impact modifier, can be used. Nevertheless, most of polymeric blends are incompatible and immiscible, i.e., show a mutual and limited solubility and in most of cases, a high interfacial tension. However, there is a relatively low interfacial tension (force which acts on transformation of a continuous structure in a dispersion) between PP and EPDM (approximately 0.3 mN.m-1), reducing the rate of breakup and facilitating the build-up of a continuous structure. This work aims to the study of compatibility of PP and EPDM blends and variation of mechanical properties, emphasizing that many properties of thermoplastic elastomers can be processed according with conventional thermoplastics methods: herein, PP/EPDM blends, 90/10, 80/20, 70/30 and 50/50 were characterized according to: Mechanical essays, Differential Scanning Calorimetry, Thermogravimetric Analyses, Melt Flow Index, Izod Impact Strength and Dynamic mechanical Analyses.